Pengaruh Pendidikan, Pelatihan, Beban Kerja, Pengalaman Kerja, dan Pemahaman Standar Akuntansi Pemerintahan terhadap Kemampuan Penyusunan Laporan Keuangan oleh Pejabat Penatausahaan Keuangan pada Satuan Kerja Perangkat Daerah di Lingkungan Pemerintah kabupaten Aceh Utara - Dede Suryani (Jurnal Telaah dan Riset Akuntansi, 2017)
This study aimed to examine the effect of education, training, workload, work experience and understanding of government accounting standards on the ability to prepare financial statements by Financial Administration Officer (PPK) in the working Unit of the Local Governments of North Aceh Regency either simultneously or partially. The population in this study were 63 respondents including the Financial Administration Officer (PPK) in SKPD in North Aceh regency.. Data used in this study were primary data through questionnaires. Data analysis method used was multiple linear regression analysis. The results showed that education, training, workload, work experience and understanding of government accounting standards influenced the ability to prepare the financial statements by Financial Administration Officer (PPK) either simultaneously or partially  on SKPD in North Aceh regency government environment. Thus, all the results of this study support the hypothesis.KEYWORDS :  Education, Training, Workload, Work Experience, Understanding of Government  Accounting Standards and The Ability of the Financial Statements by The Apparatur.